The Effect of Using a Dose of Prophylactic Antibiotics on Spondylodiscitis in Lumbar Disc Surgery - Diren, Furkan; Onal, Mehmet Bulent; Can, Halil; Kircelli, Atilla (GALENOS YAYINCILIK, 2020)
Objective: Although spondylodiscitis seen after lumbar discectomy is very rare, its incidence has been reported to be around 0.1-18.8\% by many different authors. The most common pathogen is Staphylococcus aureus. Methods: Medical records of 1,154 patients who were operated in our hospital between 2007 and 2015 due to a single or two-level lumbar disc hernia were retrospectively extracted. Of these patients, 554 were female and 600 were male. Discectomy operation was performed in 1,062 of these patients with single-level and 91 with two-level lumbar microdiscectomy. All of these patients were given a prophylactic single dose of cefazolin sodium in accordance with the recommendations of the surgical antimicrobial prophylaxis guidelines during anesthesia. Spondylodiscitis developed in 12 patients (1.03\%). Comorbidities in patients who developed spondylodiscitis, isolated pathogens, antibiotic susceptibility, antibiotics used, and hospital stay were noted. Results: Of the 12 patients, 7 were female and 5 were male. Mean age was 45.75 +/- 14.16 years. Eleven of these patients underwent single level, one had 2 levels of lumbar microdiscectomy. Five patients underwent discectomy at L4-5 and 8 patients at L5-S1 levels. Three of these patients had S. aureus (25\%), 4 had Staphylococcus epidermidis (33\%) and 3 had Escherichia coli (25\%) and 2 patients had no reproduction. The mean hospital stay was 29.45 +/- 3.98, and in patients without spondylodiscitois it was 1.99 +/- 0.81, the two groups were significantly different from each other (p=0.0001). Conclusion: Although most surgeons nave a tendency to maintain antibiotic prophylaxis postoperatively or during hospitalization period, our study found that a single dose prophylactic antibiotic administered during anesthesia induction did not increase rate of spondylodiscitis by medical literature.
Keywords: Spondiylodiscitis; lumbar microdiscectomy; Staphylococcus aureus